A Student Doctor's Guide to Tanzania - Dietrich Büsselberg (11008857) (2024)
Editors Dietrich Büsselberg (Editor & Photographer), Christine Gaskell (Co-Editor for text), and Ben Gaskell (Co-Editor for graphic design) This book features photos depicting Tanzania's rich cultural tapestry, which is as captivating as Tanzania's natural beauty. From the Masai's colorful attire and famous tribal dances to the beautiful rhythmic melodies of Swahili music, the diversity in traditions, compounded with more than 120 local languages, showcases the harmonious coexistence of multiple ethnic groups in the United Republic of Tanzania. Through this photo book, Dr. Büsselberg and the pre-medical students share their extraordinary journey during their medical service-learning trip to the United Republic of Tanzania. They take us on a unique path, where the group is immersed in the reality of the ground, visiting local villages and markets. These encounters offer a direct connection with the people and their age-old customs, while also participating in the provision of health-related services. These experiences, a blend of practical training in health services and tourism, not only provide the students with diverse perspectives and unforgettable memories of warm hospitality but also forge everlasting friendships with the people of the United Republic of Tanzania. As you delve further into this photo book, you will glimpse the challenges of the country's health sector. The students witnessed these challenges first-hand during their medical social responsibility activities in the areas they visited. The reader will also get a taste of what Tanzania has to offer through the eyes of the students, following their unforgettable safari experiences. You will witness how the country cares for its diverse wildlife and gain a deep appreciation of the local arts, traditions, and cultural practices. H.E. Habibu Awesi Mohamed, Ambassador Extraordinary and Plenipotentiary of the United Republic of Tanzania to the State of Qatar 1st English edition. Other Information Edited by: Dietrich Büsselberg, Christine Gaskell, Ben Gaskell License: http://creativecommons.org/licenses/by/4.0/ See book on publisher's website: https://doi.org/10.5339/wcm-q.9789927170423